2018
DOI: 10.1093/eurheartj/ehx794
|View full text |Cite
|
Sign up to set email alerts
|

Sudden death in patients with Ebstein anomaly

Abstract: Patients with EA are at significant risk for SD. Key clinical SD predictors identified can aid in risk stratification and potentially guide primary prevention ICD implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 25 publications
3
17
1
2
Order By: Relevance
“…In addition, ≈30% received ICDs for sudden cardiac death prevention. This is overall consistent with prior studies highlighting the propensity for both bradyarrhythmias 3 and tachyarrhythmias 1 in patients with EA.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, ≈30% received ICDs for sudden cardiac death prevention. This is overall consistent with prior studies highlighting the propensity for both bradyarrhythmias 3 and tachyarrhythmias 1 in patients with EA.…”
Section: Discussionsupporting
confidence: 92%
“…All-cause death occurred more frequently in patients with AF, but it did not remain an independent predictor after adjusting for other covariates. Although some studies have reported an association between AF and mortality in adults with CHD,14–16 other studies focused exclusively on patients with EA did not observe this association similar to our study 7 23 28 29. This might suggest that risk of death in EA derives from a complex interaction of several factors, among which AF might play a less significant role.…”
Section: Discussioncontrasting
confidence: 51%
“…No significant differences were found between the different groups of CHD, but strong trends suggest a prominent risk for severe arrhythmia in patients with Ebstein’s anomaly, while the risk in patients with a common arterial trunk appeared to be negligible. Recent studies suggest that EBS patients are at significant risk for arrhythmias and sudden cardiac death [ 27 , 28 , 29 ]. It has been stated that these lethal arrhythmias in Ebstein’s anomaly are caused by the anatomic proximity of the structural abnormalities to the conduction system, namely the tricuspid annulus, the central fibrous body, the atrioventricular (AV) node, the right-sided myocardium, and the papillary muscles [ 30 ].…”
Section: Discussionmentioning
confidence: 99%